2016
DOI: 10.4081/aiua.2016.2.111
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of enuresis nocturna and adenoid hypertrophy

Abstract: In this study we found that half of the children with EN had tonsillar hypertrophy, which was significantly higher than in the control group. Further studies are needed to clarify the exact relationship between UAO and EN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Aydın S et al (5) reported in a study they carried on 1132 children aged between five and fourteen years that there was no significant relationship between AV and PNE. In contrast to this study, Balaban M et al (6) reported in a study of 143 children in total that, ATH was observed more common in children with PNE complaints. In our study, AH and TH ratio were found significantly higher in children with PNE.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Aydın S et al (5) reported in a study they carried on 1132 children aged between five and fourteen years that there was no significant relationship between AV and PNE. In contrast to this study, Balaban M et al (6) reported in a study of 143 children in total that, ATH was observed more common in children with PNE complaints. In our study, AH and TH ratio were found significantly higher in children with PNE.…”
Section: Discussioncontrasting
confidence: 97%
“…As a matter of fact, it is known that children with PNE have difficulty in waking up for toilet (12). Balaban M et al (6) reported in their study that sleep is deeper in children with PNE. Nevertheless, ATH also causes a decrease in sleep quality by leading upper airway resistance and sleep apnea in children (13).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[6][7][8][9] Previous studies have documented that the prevalence of enuresis is 22-42% among children with adenoid hypertrophy and 8-47% among children with upper airway obstruction, with prominent improvement of enuresis after surgery. [6,9,10] Regarding the relationship between nocturnal enuresis and adenoid hypertrophy, it has been emphasized that nocturnal enuresis may be a symptom, sign and result of adenoid hypertrophy [6][7][8][9] , and that the relationship has been mainly linked to sleep pathologies and upper airway obstruction caused by adenoid hypertrophy. It is highlighted that upper airway obstruction and sleep apnea increase water and sodium excretion by increasing the nighttime release of atrial natriuretic peptide due to the stimulation of right atrial receptors originating from alterations of intrathoracic pressure, which in turn, can cause enuresis.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have advocated the role of upper airway obstruction in PNE etiology, some others have not. [3][4][5][6] Furthermore, to the best of our knowledge, there is no study regarding this subject in which the degree of nasal obstruction is determined by objective methods.…”
mentioning
confidence: 99%